Thermal Correction to the Kinnersley Black Hole in a Lorentz-Violating Dirac Field Theory - Liu, Zhi-E.; Zhang, Jie; Yang, Shu-Zheng (Frontiers in Physics, 2021)
According to Lorentz-violating theory, the dynamical equation of Dirac particles in the Kinnersley black hole with variably accelerated linear motion is modified. The Hawking quantum tunneling radiation characteristics of Kinnersley black hole are obtained by solving the modified equation. The expression of the Hawking temperature of Kinnersley black hole has been updated.